Hyperglycemia Management Using Progressive Muscle Therapy in Diabetes Mellitus Patients: Case Study - Rahma, Natasya Widya; Munika, Evi; Asmorosari, Fitria; Maghfiroh, Azizatul; Fitrianti, Rizqi Indah; Efendi, Muhammad Zufar; Lestari, Trijati Puspita; Firdaus, Andhika Wahyu (Jurnal Surya, 2024)
Introduction: Diabetes Mellitus is a condition when blood sugar levels are in the high category or commonly called hyperglycemia, high blood sugar levels can cause several problems that often arise and can cause several complications that occur. The limited implementation of non-pharmacological progressive muscle relaxation therapy is the basis for the implementation of this research. The purpose of this study was to analyze the management of hyperglycemia in patients with Diabetes Mellitus. Method: Case study design method was used in the study with three clients, namely patients with Diabetes Mellitus. The action given to overcome this with progressive muscle relaxation therapy given 3 times for 3 consecutive days t. This study was conducted at Aisyiyah Hospital Bojonegoro in September 2023. The analysis was carried out using the SMART method (specific, measurable, achievable, relevant and time-bound goals). The FIKes UMLA Medical Surgical Nursing Care format was used in the data collection process to action evaluation. Results: The results of the case study showed that on the first day of the assessment of the three patients, blood glucose was found to be in the high category. After 3 days, nursing problem of blood glucose instability was resolved, blood glucose levels improved , drowsiness decreased sufficiently, dizziness decreased , fatigue/lethargy decreased sufficiently and complaints of hunger decreased . Conclusion: Progressive Muscle Relaxation Therapy is effective in lowering blood glucose levels. This therapy can be combined with pharmacological therapy such as insulin and oral medications and other treatments needed by patients with diabetes mellitus so that it can help medical personnel in stabilizing blood sugar levels in patients with diabetes mellitus.